Development and Evaluation of a Novel Diammonium Glycyrrhizinate Phytosome for Nasal Vaccination - Xiaojin Chen; Xudong Fan; Fanzhu Li (MDPI AG, 2022)
The objective of the present research was to formulate diammonium glycyrrhizinate (DG) into phytosomes (DG-P) to induce nasal immune responses and enhance absorption. Plackett- Burman design was used for process optimization, incorporating specific formulation and process variables to obtain the optimal parameters. Fourier transform infrared spectroscopy (FTIR), X-ray power diffraction (P-XRD), and transmission electron microscopy (TEM) were used for characterization. The adjuvant activity of the DG-P was evaluated by using bone marrow dendritic cells. In vitro nasal mucosal permeation and in situ nasal perfusion were also investigated to evaluate nasal absorption. The DG phytosomes were in the size range of 20~30 nm and zeta-potential range of −30~−40 mV. DG-P demonstrated 4.2-fold increased solubility in n-octanol. Coculturing bone marrow dendritic cells with DG-P led to enhanced dendritic cell maturation. Apparent permeability coefficient of the phytosomal formulation was almost four times higher than that of free DG determined by ex vivo permeation studies on excised porcine mucosa. In situ nasal perfusion studies in rats demonstrated that the nasal absorption of DG-P was significantly higher than that of free DG. Conclusively, the results confirmed that DG-P have potential for use as an adjuvant for nasal vaccine.